Research on the Design of Digital Virtual Display Space for the haihun Marquis Chariot and Horses Based on Multidimensional Interaction Technology - Dai, Yijun; Yi , Fengyu (Journal of Ecohumanism, 2024)
This research employs qualitative descriptive analysis to explore the display needs of the Han Dynasty haihun Marquis tomb’s chariot and horse relics in Nanchang. It investigates how the design of a chariot-and-horse-style digital virtual exhibition hall, leveraging digital media technologies, can present the historical stories behind these artifacts. The aim is to create a new online virtual exhibition experience that effectively promotes the integration and development of the cultural and tourism industries. Ultimately, it seeks to achieve a win-win fusion of cultural and economic innovation by merging online virtual spaces with historical culture.